Persons, interests, and justice - Holtug, Nils, 1964- (Oxford : Oxford University Press, 2010)
In our lives, we aim to achieve welfare for ourselves, that is to live good lives. But we also have another, more impartial perspective, where we aim to balance our concern for our own welfare against a concern for the welfare of others. This is a perspective of justice. Nils Holtug examines these two perspectives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Conduct of life; Justice; Well-being.